A Study of Quality of Work Life of Nationalized and Non Nationalized Bank Employees - S, Triveni; A. Amminabhavi, Vijayalaxmi (Ushus Journal of Business Management, 2005)
The objective of the present study is to determine scientifically the level of quality-of-work-life (QWL) of nationalized and non-nationalized bank employees and also to find out the significance of difference between nationalized and non-nationalized bank employees in their QWL. To achieve this objective, The Quality of Work Life-Condition/ Feelings form was administered on a sample of 78 bank employees of which 39 are from nationalized and 39 from non-nationalized banks in Hubli—Dhaiwad Corporation area. The obtained responses were scored and subjected to t-test. The results revealed that the nationalized bank employees have significantly higher QWL than those of non-nationalized bank employees in the dimensions like- autonomy, Work speed and Routine, Work complexity as well as the composite QWL—Conditions. The incidental analyses in the study revealed that the bank employees who expressed higher life satisfaction have shown significantly higher QWL with regard to conditions than those who expressed moderate life satisfaction.